Understanding Role Expectations in High School Students' Readiness for Family Life: Pemahaman Harapan Peran dalam Kesiapan Siswa SMA untuk Kehidupan Keluarga - F.A. Akramova (Academia Open, 2023)
This article aims to investigate the psychological features of high school students' readiness for family life by analyzing the results of the "Role Expectations and Claims in Marriage" (ROP) method developed by A.N. Volkova. The study shows that the well-being of the family largely depends on the degree of understanding by the spouses of their family roles, upon which relationships are built. The analysis of the ROP method results reveals that high school students have a significant gap in their understanding of family roles and expectations, which might affect their readiness for family life. The implications of this study highlight the importance of preparing high school students for family life by developing their understanding of family roles, which could lead to better family relationships and ultimately improve the well-being of the family as a whole. Highlights: Understanding of family roles is critical for building healthy family relationships. High school students often lack a clear understanding of family roles and expectations. The ROP method is an effective tool for assessing high school students' readiness for family life. Keywords: psychology, family roles, high school students, readiness, ROP method.